Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd004818.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for acute coronary syndrome

Abstract: For people with ACS, there is some evidence from small trials to suggest that HBOT is associated with a reduction in the risk of death, the volume of damaged muscle, the risk of MACE and time to relief from ischaemic pain. In view of the modest number of patients, methodological shortcomings and poor reporting, this result should be interpreted cautiously, and an appropriately powered trial of high methodological rigour is justified to define those patients (if any) who can be expected to derive most benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Again, an appropriately powered trial of high methodological rigour is required to define those patients (if any) who can be expected to derive most benefit from HBO. At present, its routine application cannot be justified .…”
Section: Oxygen Treatment In Diseased Statesmentioning
confidence: 99%
“…Again, an appropriately powered trial of high methodological rigour is required to define those patients (if any) who can be expected to derive most benefit from HBO. At present, its routine application cannot be justified .…”
Section: Oxygen Treatment In Diseased Statesmentioning
confidence: 99%
“…Hyperbaric oxygen therapy is a safe procedure defined by the Undersea and Hyperbaric Medical Society as a treatment where 100% O 2 is breathed inside a pressurized chamber in which the pressure is higher than 1 absolute atmosphere (101 kPa) 6 . Previous studies have analysed the myocardial protective effects of HBO on ischaemia–reperfusion injury in both animal models 7–10 and humans 11–13 . To the best of our knowledge, only one study 8 evaluated the effect of HBO on MI 24 h after occlusion and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hs-CRP, a maker of the inflammatory response involved in many types of acute and chronic physiological inflammation, is thought to be closely related to SCF onset [10,11]. According to Bennett's report [15], HBO treatment can reduce myocardial ischemia and mortality rate of patients suffering from acute coronary syndrome. Another study from Khan et al [16] showed that HBO treatment can increase myocardial oxygen supply, and enhance the expression of vascular endothelial growth factors and the recovery of cardiomyocytes, and can also significantly improve the efficacy of stem-cell transplantationtreated myocardial infarct rats.…”
Section: Discussionmentioning
confidence: 99%